Do More Powerful Interest Groups have a Disproportionate Influence on Policy? - Zara Sharif; Otto H. Swank (Tinbergen Institute, 2012)
Decisions-makers often rely on information supplied by interested parties. In practice, some parties have easier access to information than other parties. In this light, we examine whether more powerful parties have a disproportionate influence on decisions. We show that more powerful parties influence decisions with higher probability. However, in expected terms, decisions do not depend on the relative strength of interested parties. When parties have not provided information, decisions are biased towards the less powerful parties. Finally, we show that compelling parties to supply information destroys incentives to collect information.
urn:NBN:nl:ui:15-1765/38214
Keywords: D72; D78; D82; H39; 330; information collection; communication; interest groups; decision-making; Interessenvertretung; Macht; Informationsverbreitung; Asymmetrische Information; Partizipation; Neue politische Ökonomie; Theorie